The Use of Budesonide in the Treatment of Autoimmune Hepatitis in Canada. (2008) - Zandieh, Iman; Krygier, Darin; Wong, Victor; Howard, John; Worobetz, Lawrence; Minuk, Gerald; Witt-Sullivan, Helga; Yoshida, Eric M
Abstract : BACKGROUND: Autoimmune hepatitis (AIH) is a chronic inflammatory disease that is successfully treated with prednisone and/or azathioprine immunosuppressive therapy in 70% to 80% of patients. The remaining patients are intolerant or refractory to these standard medications. Budesonide, a synthetic glucocorticoid, undergoes a high degree of first-pass metabolism, reducing its systemic bioavailability, and has a 15-fold greater affinity for the glucocorticoid receptor than prednisolone. Budesonide may be a potentially useful systemic steroid-sparing immunosuppressive agent in the treatment of AIH. OBJECTIVE: To review the Canadian experience using budesonide to treat AIH. METHODS: Patients with AIH currently or previously treated with budesonide were identified through the Canadian Association for the Study of the Liver membership. Data were collected regarding their clinical and treatment history. RESULTS: A total of nine patients were identified. All patients were female, with an average age of 39 years (range 12 to 66 years). The indications for budesonide were adverse side effects of prednisone in two patients, noncompliance with prednisone and azathioprine in one patient and intolerance to azathioprine resulting in prednisone dependence in the remaining six patients. Patients were treated in doses ranging from 9 mg daily to 3 mg every other day for 24 weeks to eight years. Seven of nine patients had a complete response, defined as sustained normalization of the aminotransferase levels. The remaining two patients were classified as nonresponders (less than a 50% reduction in pretreatment aminotransferase levels). CONCLUSIONS: In Canada, budesonide has been successfully used in seven of nine patients with autoimmune hepatitis who were either intolerant to prednisone and azathioprine or prednisone-dependent. No adverse effects were reported with budesonide. Budesonide is potentially a valuable treatment option for AIH patients refractory or intolerant to standard therapy, and is deserving of further study.